GNAO1 encephalopathy: Broadening the phenotype and evaluating treatment and outcome. (April 2017) - Danti, Federica Rachele; Galosi, Serena; Romani, Marta; Montomoli, Martino; Carss, Keren J.; Raymond, F. Lucy; Parrini, Elena; Bianchini, Claudia; McShane, Tony; Dale, Russell C.; Mohammad, Shekeeb S.; Shah, Ubaid; et al.
Abstract : Objective: To describe better the motor phenotype, molecular genetic features, and clinical course of GNAO1 -related disease. Methods: We reviewed clinical information, video recordings, and neuroimaging of a newly identified cohort of 7 patients with de novo missense and splice site GNAO1 mutations, detected by next-generation sequencing techniques. Results: Patients first presented in early childhood (median age of presentation 10 months, range 0–48 months), with a wide range of clinical symptoms ranging from severe motor and cognitive impairment with marked choreoathetosis, self-injurious behavior, and epileptic encephalopathy to a milder phenotype, featuring moderate developmental delay associated with complex stereotypies, mainly facial dyskinesia and mild epilepsy. Hyperkinetic movements were often exacerbated by specific triggers, such as voluntary movement, intercurrent illnesses, emotion, and high ambient temperature, leading to hospital admissions. Most patients were resistant to drug intervention, although tetrabenazine was effective in partially controlling dyskinesia for 2/7 patients. Emergency deep brain stimulation (DBS) was life saving in 1 patient, resulting in immediate clinical benefit with complete cessation of violent hyperkinetic movements. Five patients had well-controlled epilepsy and 1 had drug-resistant seizures. Structural brain abnormalities, including mild cerebral atrophy and corpus callosum dysgenesis, were evident in 5 patients. One patient had a diffuse astrocytoma (WHO grade II), surgically removed at age 16. Conclusions: Our findings support the causative role of GNAO1 mutations in an expanded spectrum of early-onset epilepsy and movement disorders, frequently exacerbated by specific triggers and at times associated with self-injurious behavior. Tetrabenazine and DBS were the most useful treatments for dyskinesia.